Football in computer-mediated discourse: A move analysis of match previews - Nartey, Mark (Linguistik Online, 2018)
In the last couple of decades, linguistic enquiry into internet genres has become prevalent, resulting in the investigation of internet genres such as live-text commentary, weblogs, online news/news websites, and social network sites. In tandem with this research tradition, the current study investigated the football match preview in a bid to identify its schematic structure and the rhetorical strategies deployed by producers of this genre in achieving their communicative goal(s). Six match previews taken from two online sports websites, Goal.com and Sky-sports.com, comprised the data for the study and Swales’ (1990; 2004) framework of move analysis was used to analyse the data. The study found that the match preview employed a six-move pattern, namely naming the contest, pre-contest dynamics, predicting team line-ups and team formations, assessing squad strength, discussing the contest and naming the preview author. These moves were found to be realised by a relatively restricted range of lexico-grammatical resources. This study has implications for the construction of the match preview genre and future genre studies.